Analysis of effects of aerodynamic interference on dynamic response of suspended monorail wind–vehicle–bridge system using joint simulation approach. (November 2022) - Zou, Yunfeng; Liu, Zhipeng; Shi, Kang; He, Xuhui; Zhou, Shuai; Ma, Wenrong
Abstract: A dynamic simulation model of a suspended monorail vehicle–bridge system was developed using a joint simulation approach based on ANSYS and SIMPACK. Moreover, the aerodynamic coefficients of the vehicle–bridge system were measured through a wind-tunnel test, in which a wind load was applied as an external excitation. The variation law of the dynamic response of a double-line suspended monorail vehicle–bridge system with respect to the line spacing under aerodynamic interference was systematically studied, and the following results were obtained. (1) The effect of the vehicle–bridge combination on the aerodynamic coefficient was significant. In the case of one vehicle, the vehicle on the downstream line was slightly less affected by the crosswind than that on the upstream line. For these two vehicles, the three-component force coefficient of the downstream vehicle was far smaller than that of the upstream vehicle. (2) In the case of two vehicles, an increase in the spacing ratio reduced the drag of the vehicles. When the spacing ratio exceeded 4.5, the change in the three-component force of the upstream vehicle was no longer obvious, but the drag value for the downstream vehicle changed from negative to positive. (3) With an increase in the spacing ratio, the vehicle acceleration generally increased, but the changes in the acceleration and displacement of the bridge were insignificant. (4) During the meeting of two vehicles, the vehicle running on the upstream side is easy to be affected by winds than on the downstream side, which leads to the result that the dynamic response of the upstream vehicle and bridge are larger than that of the downstream side.